Perancangan Strategi E-Commerce Berbasis Website Untuk Meningkatkan Penjualan Kerajinan Perak Di Koto Gadang Bukittinggi - Aqil Ramadhan, Muhammad; Akhiyar, Dinul; Wisky, Irzal Arief (Riset Sinergi Indonesia, 2025)
The rapid development of information technology has driven the need for a system that can simplify operational management in various sectors, including managing ordering and payments at Toko Perak Koto Gadang. This research aims to design and implement a web-based queue ordering and payment information system using the PHP programming language and MySQL database. This system is expected to be able to provide convenience for customers in ordering online, as well as for Toko Perak Koto Gadang managers in managing and monitoring the use of available infrastructure. This system design process includes the stages of requirements analysis, system design, implementation and testing. This system is designed with a user-friendly interface, so that it can be used by various groups easily. With this system, it is hoped that it can reduce customer waiting times, increase operational efficiency, and provide a better service experience. The test results show that the system runs well and meets user needs. Thus, this information system can be implemented effectively at Toko Perak Koto Gadang to support more structured and efficient ordering and payment management.